50.0k views
5 votes
Yalll n-4 = 3n + 6 do me a favah

User LudoMC
by
5.1k points

2 Answers

5 votes

Answer:

n=-5

Explanation:

-4=2n+6

-10=2n

-5=n

User Artjom
by
5.2k points
3 votes

Answer:

n=-5

n

-

4

=

3

+

6

n-4=3n+6

n−4=3n+6

Solve

1

Add

4

4

4

to both sides of the equation

4

=

3

+

6

n-4=3n+6

n−4=3n+6

4

+

4

=

3

+

6

+

4

n-4+{\color{#c92786}{4}}=3n+6+{\color{#c92786}{4}}

n−4+4=3n+6+4

2

Simplify

3

Subtract

3

3n

3n

from both sides of the equation

4

Simplify

5

Divide both sides of the equation by the same term

6

Simplify

User Adam Naylor
by
5.1k points